(untitled) (Applied Biological Research, 2020)
The sustainability of sericulture industry depends on the growth of silkworm which, in turn, depends on the leaf quality of mulberry on which the silkworms feed. To meet the feed demands of silkworm, it is essential to evolve high yielding mulberry varieties possessing high quality nutritive leaves as well as the ability to grow under varied agro-climatic conditions throughout the year. Silkworm is a monophagous insect, therefore the carbohydrate and protein contents in mulberry foliage play vital role in quality silk production. Young silkworms require succulent leaves for easy ingestion, while late-age silkworms can feed on mature leaves as they have the strength to cut and ingest the hard leaves which usually possess less proteins and water (Srichaikul et al., 2011). The availability of moisture content in leaves enhances the feeding efficiency of silkworm larvae which, in turn,